Real-life Task in Mathematics Teaching: A Case of Statistics Teaching in Order to Educate some Economic Knowledge for Students at High School - Trung, Nguyen Tien; Giang, Pham Anh; Tinh, Phan Thi (VNU Journal of Science: Education Research; Vol 36 No 2DO - 10.25073/2588-1159/vnuer.4412, 2020)
Real-world connections in mathematics teaching is a requirement and a trend in teaching mathematics in high schools in Vietnam. The commentary on the “reality” and the exploitation of “real-life task” in mathematics teaching is still not much clear. This research contributes to giving perspectives on “real-life task” and their exploitation and use in teaching mathematics through a specific case: teaching statistics in high schools to contribute to educating some economic knowledge for students. The mathematical task classification and analysis framework proposed the relationship with the real-life task in the article will give teachers and researchers to have an approach in exploiting real-life tasks in mathematics teaching.